2004
DOI: 10.1038/sj.ejcn.1602048
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin C in breast milk may reduce the risk of atopy in the infant

Abstract: Objective: To assess the effects of maternal dietary and supplement intake of vitamins C and E on breast milk antioxidant composition (vitamin C, a-tocopherol and b-carotene) and their protective potential against the development of atopy in the infant. Design, subjects and methods: Mothers with atopic disease were recruited at the end of gestation and maternal sensitization was assessed by skin-prick testing. The 4-day food records of the mothers and breast milk samples were collected at the infants' age of 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
37
1
9

Year Published

2007
2007
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 73 publications
(51 citation statements)
references
References 29 publications
1
37
1
9
Order By: Relevance
“…[31][32][33] However, the evidence that breastfeeding prevents allergies is contradictory, with some reviews showing a benefit while others did not. [34][35][36][37][38] These findings may be due to variations in breast milk composition, differences in maternal diet, [39][40][41][42] differences in specific infant-feeding practices, or a lack of precision in the way infant feeding has been measured. However, another explanation is that the immunomodulatory role of breast milk is only apparent when the immune system is exposed to an antigen at the same time as breast milk (the "overlap" effect).…”
Section: Discussionmentioning
confidence: 83%
“…[31][32][33] However, the evidence that breastfeeding prevents allergies is contradictory, with some reviews showing a benefit while others did not. [34][35][36][37][38] These findings may be due to variations in breast milk composition, differences in maternal diet, [39][40][41][42] differences in specific infant-feeding practices, or a lack of precision in the way infant feeding has been measured. However, another explanation is that the immunomodulatory role of breast milk is only apparent when the immune system is exposed to an antigen at the same time as breast milk (the "overlap" effect).…”
Section: Discussionmentioning
confidence: 83%
“…Several previous studies have reported the beneficial association of dietary antioxidant vitamins with the risk of atopic diseases (39)(40)(41). For example, a higher concentration of vitamin C in breast milk is associated with a reduced risk of AD in infants (ORs0.30, 95% CI 0.09-0.94) (42). Further studies to identify potential interactions between dietary antioxidant intake and GSTP1 genotype in the risk of AD are needed.…”
Section: Discussionmentioning
confidence: 99%
“…However neither of these studies adjusted their results for potential confounders. In another unadjusted study [47], increased vitamin C concentration in atopic mothers' breast milk (attributed to dietary intake of vitamin C from fruit and vegetables during lactation) was associated with significantly reduced rates of eczema in their children.…”
Section: Observational Studiesmentioning
confidence: 99%
“…Judging by occurrence of atopic eczema and positive skin prick testing, Hoppu [47] described a decreased risk of atopy at 1 year of age, with increasing vitamin C in breast milk -which reflected maternal intake of fruits and vegetables.…”
Section: Dietary Associations -Individual Foodsmentioning
confidence: 99%